Assessing dose rate distributions in VMAT plans. (29th March 2016) - Mackeprang, P-H; Volken, W; Terribilini, D; Frauchiger, D; Zaugg, K; Aebersold, D M; Fix, M K; Manser, P
Abstract: Dose rate is an essential factor in radiobiology. As modern radiotherapy delivery techniques such as volumetric modulated arc therapy (VMAT) introduce dynamic modulation of the dose rate, it is important to assess the changes in dose rate. Both the rate of monitor units per minute (MU rate) and collimation are varied over the course of a fraction, leading to different dose rates in every voxel of the calculation volume at any point in time during dose delivery. Given the radiotherapy plan and machine specific limitations, a VMAT treatment plan can be split into arc sectors between Digital Imaging and Communications in Medicine control points (CPs) of constant and known MU rate. By calculating dose distributions in each of these arc sectors independently and multiplying them with the MU rate, the dose rate in every single voxel at every time point during the fraction can be calculated. Independently calculated and then summed dose distributions per arc sector were compared to the whole arc dose calculation for validation. Dose measurements and video analysis were performed to validate the calculated datasets. A clinical head and neck, cranial and liver case were analyzed using the tool developed. Measurement validation of synthetic test cases showed linac agreement to precalculated arc sector times within  ±0.4 s and doses  ±0.1 MU (one standard deviation). Two methods for the visualization of dose rate datasets were developed: the first method plots a two-dimensional (2D) histogram of the number of voxels receiving a given dose rate over the course of the arc treatment delivery. In similarity to treatment planning system display of dose, the second method displays the dose rate as color wash on top of the corresponding computed tomography image, allowing the user to scroll through the variation over time. Examining clinical cases showed dose rates spread over a continuous spectrum, with mean dose rates hardly exceeding 100 cGy min −1 for conventional fractionation. A tool to analyze dose rate distributions in VMAT plans with sub-second accuracy was successfully developed and validated. Dose rates encountered in clinical VMAT test cases show a continuous spectrum with a mean less than or near 100 cGy min −1 for conventional fractionation.